2022
DOI: 10.1039/d1ra08525e
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of a binary S-scheme S-g-C3N4/Co-ZF heterojunction with enhanced spatial charge separation for sunlight-driven photocatalytic performance

Abstract: A novel S-scheme photocatalyst system is constructed utilizing the hydrothermal technique and S-g-C3N4/Co-ZF binary material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In another study, they also reported that photocorrosion of zinc oxide was inhibited by doping Ni in the ZnO nanostructure . A step-scheme photocatalyst made of sulfurized graphitic carbon nitride/cobalt-doped zinc ferrite (S- g -C 3 N 4 /Co-ZF) was also reported by this group using a hydrothermal process …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In another study, they also reported that photocorrosion of zinc oxide was inhibited by doping Ni in the ZnO nanostructure . A step-scheme photocatalyst made of sulfurized graphitic carbon nitride/cobalt-doped zinc ferrite (S- g -C 3 N 4 /Co-ZF) was also reported by this group using a hydrothermal process …”
Section: Introductionmentioning
confidence: 85%
“…16 A step-scheme photocatalyst made of sulfurized graphitic carbon nitride/ cobalt-doped zinc ferrite (S-g-C 3 N 4 /Co-ZF) was also reported by this group using a hydrothermal process. 17 Various cobalt-substitution ratios (SFCM, x = 0, 0.5, 0.75, and 1) were chosen as the pioneering method to assess SOFC efficacy in H 2 −H 2 S. Investigations into the results of cobalt replacement on the electrochemical, catalytic, and crystallite structures led to a better understanding of the structural flaws in SFCM brought on by cobalt doping. In a reducing environment, a series of cobalt-substituted SFCM (x = 0, 0.5, 0.75, and 1) were created, and their double-perovskite structures were established.…”
Section: Introductionmentioning
confidence: 99%